YOUTH WORKERS’ EXPERIENCE REGARDING SEXUAL AND REPRODUCTIVE HEALTH EDUCATION IN SECONDARY SCHOOLS - Chauke, Thulani Andrew (International Journal of Child, Youth and Family Studies, 2024)
The alarming prevalence of HIV/AIDS and unwanted pregnancy among learners is of considerable concern. This study aimed to explore the barriers encountered by youth workers in implementing sexual and reproductive health education (SRHE) in secondary schools South Africa in the Western Cape province of South Africa and also to explore the benefits these youth workers bring. Qualitative methods and individual interviews were used to gather data. The findings show that cultural socialisation remains a major barrier to the effective implementation of SRHE by youth workers. Positive outcomes from the presence of the youth workers in schools include an increase in learners’ self-esteem and greater acceptance of moral values such as good citizenship and respect for others regardless of differences. Accordingly, this study recommends integrating youth workers into the schools by adding SRHE to the curriculum and having it implemented by them. When such programmes are set up, the role of youth workers in schools should be clearly articulated to avoid conflict between teachers and youth workers.